REALITAS KEHIDUPAN PEKERJA ANAK: (Studi Tentang Pekerja Anak Putus Sekolah di Pasar Sentral Kota Gorontalo). - Arten H. Mobonggi (Irfani, 2017)
The purpose of the writing are to describe the reality of life of schoolchild workers especially in the central market area of Gorontalo. The object of the writing was schoolchild workers who work in central market It used the social culture approach of Gorontalo society who has diligent in their work. Based on the result of the research show that the causal factor of the schoolchild workers existence in central market of Gorontalo caused by a poverty situation, it’s declining of religion moral value in family, settlement base has not place play for them. Beside that it was caused by the improving of the economic growth that refer to industrialization and it closed for them. So they were prefer work in the traditional market than in other place because it was deemed as money reputation.